A descriptive analysis of pediatric post-tonsillectomy pain and recovery outcomes over a 10-day recovery period from 2 randomized, controlled trials. (6th March 2020) - Postier, Andrea C.; Chambers, Christine; Watson, David; Schulz, Craig; Friedrichsdorf, Stefan J.
Abstract: Pediatric tonsillectomy involves an often painful and lengthy recovery period, yet the extended recovery process is largely unknown. This article describes postoperative recovery outcomes for 121 children aged 4 to 15 (mean 6.6 years, SD = 2.3) years enrolled in 1 of 2 clinical trials of analgesia safety and efficacy after tonsillectomy. Postoperative analgesia included scheduled opioid analgesic plus acetaminophen/ibuprofen medication use (first 5 days) and "as-needed" use (last 5 days). Clinical recovery as measured daily by the Parents' Postoperative Pain Measure (PPPM; an observational/behavioral pain measure), children's self-reported pain scores, side-effect assessments, need for unanticipated medical care, and satisfaction with recovery over 10 days was assessed. Higher Parents' Postoperative Pain Measure scores were correlated with poorer sleep, receipt of breakthrough analgesics, distressing side effects, higher self-reported pain scores, and need for unanticipated medical care. Higher self-reported pain scores were associated with more distressing adverse events, including nausea, vomiting, insomnia, lower parent satisfaction, and unplanned medical visits and hospitalizations. Pain and symptoms improved over time, although 24% of the children were still experiencing clinically significant pain on day 10. Scheduled, multimodal analgesia and discharge education that sets realistic expectations is important. This study adds to the emerging body of literature that some children experience significant postoperative pain for an extended period after tonsillectomy.